Femtosecond-laser–induced modifications in Co/Pt multilayers studied with tabletop resonant magnetic scattering. (14th January 2015) - Weier, C.; Adam, R.; Rudolf, D.; Frömter, R.; Grychtol, P.; Winkler, G.; Kobs, A.; Oepen, H. P.; Kapteyn, H. C.; Murnane, M. M.; Schneider, C. M.
Abstract: We characterize the magnetic domain structure of Co/Pt multilayer films on length scales below one hundred nanometers using resonant magnetic scattering and magnetic force microscopy. The extreme ultraviolet light for the scattering experiment is created by a laser-based high-order harmonic generation source. After illumination with intense ultrashort infrared laser pulses, we observe pronounced changes in the magnetic structure and morphology. This study points out the importance of a detailed analysis of the different laser-induced modifications of a magnetic thin film that influence the scattering patterns.